No indication of porcine reproductive and respiratory syndrome virus (PRRSV) infection in Brazilian swine herds. - ZANELLA, J. R. C. (2013)
Porcine reproductive and respiratory syndrome virus (PRRSV) is a globally important pathogen of economic and veterinary concern. Recent studies estimate a cost of US$664m yearly to United States swine industry 3. PRRS is present throughout the world, with the exception of Australia, New Zealand, Finland, Norway, Sweden and Switzerland 5. Although Brazilian swine production is expressive (fourth pork producer and exporter), there has been no evidence of PRRSV infection in those herds 1. Most of the analysis used serology by commercial ELISA tests in breeding herds to perform prevalence surveys. The objective of this work was to detect PRRSV in samples of sera, plasma or oral fluids (OF) from swine herds, quarantined imported boars and feral pigs from 2008 ? 2012.